Kingship as "Dharma-Protector": A Comparative Study of Wŏnhyo and Huizhao's Views on the Golden Light Sutra - Lee, Sumi (Journal of Korean religions, 2017)
"State-protection Buddhism" (Ch. huguo Fojiao, K. hoguk Pulgyo 護國佛敎), the idea that Buddhism protects the state from various natural as well as societal difficulties, was widely accepted in premodern East Asia. Not a few East Asian rulers who adopted Buddhism as a state ideology expected such Buddhist deities as the four heavenly kings (Skt. lokapāla, Ch. si tianwang, K. sa ch'ŏnwang 四天王) to protect the state as a result of their faith in "state-protection" scriptures, such as the Golden Light Sutra (Ch. Jinguangming jing, K. Kŭmgwangmyŏng kyŏng 金光明經). Although state-protection Buddhism has been approached focusing on its political aspect, from the Buddhist doctrinal viewpoint, state protection refers to none other than "Dharma protection" (Ch. hufa, K. hobŏp 護法), and the kings who take the responsibility of protecting the state also are protectors of the Dharma. East Asian Buddhist scholiasts, however, did not always reach consensus on the nature of kingship as Dharma protector. This article explores distinct interpretations of kingship in the Golden Light Sutra between two eminent Buddhist exegetes, Wŏnhyo 元曉 (617–686) and Huizhao 慧昭 (774–850). Although Wŏnhyo's commentary on the Golden Light Sutra, the Kŭmgwangmyŏng kyŏng so 金光明經疏, is not extant, a significant part of it is cited in Japanese monks' works, notably in Gangyō's 願曉 (835–871) Konkōmyō saishō ō kyō gensū 金光明最勝王經玄樞, and we can therefore compare it to Huizhao's commentary, the Jinguangming zuishengwang jing shu 金光明最勝王經疏. On the basis of a comparative analysis of their views on the sutra, this article discusses how the two exegetes interpret kingship in the Golden Light Sutra and reconcile the two dilemmatic concepts of commonality and particularity.